Rockfall Dynamics During Volcanic Eruptive Phases: A Statistical Assessment - Jelena Koritnik; Juan C. Santamarta; Noelia Cruz-Pérez; Matej Horvat; Luis E. Hernández-Gutiérrez; Rafael García Martín; Sergio Leyva (Salehan Institute of Higher Education, 2026)
The Canary Islands, a volcanic archipelago off the northwest coast of Africa, are frequently exposed to geohazards. The 2021 Tajogaite eruption on La Palma provided an opportunity to assess how volcanic activity and related seismicity influence rockfall dynamics. This study statistically analyzed a dataset of 1,111 road-related rockfall incidents recorded between 2019 and 2024, comparing event occurrence, severity, and lithological distribution across pre-, syn-, and post-eruption periods. Events were classified based on operational descriptors, and linked to geological units to evaluate lithological controls. While the total number of events remained nearly identical before (519) and after (517) the eruption, the normalized rate of rockfall occurrence increased during the eruptive phase. Lithological distributions also differed across periods: altered basalts consistently recorded the highest number of incidents; pyroclasts and colluvium increased syn-eruption likely due to seismic shaking; and fresh basalts declined post-eruption, suggesting prior mobilization of unstable material. This study provides empirical insight into how eruptive processes influence infrastructure-related rockfall hazards on volcanic islands characterized by steep topography and narrow, low-redundancy mountain road networks. Nevertheless, rockfalls also occurred consistently during non-eruptive periods, highlighting the need for continuous slope hazard monitoring in environments such as La Palma where both eruptive and non-eruptive processes threaten exposed infrastructure, population, and high tourist activity.